2016
DOI: 10.1186/s12864-016-3007-5
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis revealed that a quorum sensing system regulates the transfer of the pAt megaplasmid in Agrobacterium tumefaciens

Abstract: BackgroundAgrobacterium tumefaciens strain P4 is atypical, as the strain is not pathogenic and produces a for this species unusual quorum sensing signal, identified as N-(3-hydroxy-octanoyl)-homoserine lactone (3OH,C8-HSL).ResultsBy sequence analysis and cloning, a functional luxI-like gene, named cinI, has been identified on the At plasmid of A. tumefaciens strain P4. Insertion mutagenesis in the cinI gene and transcriptome analyses permitted the identification of 32 cinI-regulated genes in this strain, most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…Bioinformatic data have shown the presence of rctA and rctB homologues in the A. tumefaciens pAT plasmid, and recent transcriptomic data suggest that, at least in the pAT plasmid of strain P4, the regulation by RctA-RctB is under QS control (Mhedbi-Hajri et al, 2016;Nogales et al, 2013). A different regulatory system has been described for pESI from Salmonella enterica sv infantis (Aviv et al, 2016).…”
Section: Symbiosis and Pathogenicity Plasmidsmentioning
confidence: 95%
“…Bioinformatic data have shown the presence of rctA and rctB homologues in the A. tumefaciens pAT plasmid, and recent transcriptomic data suggest that, at least in the pAT plasmid of strain P4, the regulation by RctA-RctB is under QS control (Mhedbi-Hajri et al, 2016;Nogales et al, 2013). A different regulatory system has been described for pESI from Salmonella enterica sv infantis (Aviv et al, 2016).…”
Section: Symbiosis and Pathogenicity Plasmidsmentioning
confidence: 95%
“…Therefore, despite finding no difference in attachment or biofilm formation under laboratory conditions (Figure 2), RaiR may nevertheless play a role (via the regulation of a Atse homolog) in the initial colonization of D. pulchra. This possibility is further supported by findings that Atse expression is positively controlled by QS and is important for virulence in the plant pathogen A. tumefaciens (Matthysse, Yarnall, Boles, & McMahan, 2000;Mhedbi-Hajri et al, 2016). Previous proteomic studies indicated that the N. italica R11 gene regulator…”
Section: Atp Synthasementioning
confidence: 75%
“…A recent transcriptome analysis study showed that QS regulates conjugative transfer in Agrobacterium tumefaciens [ 46 ]. Transcriptome profiling showed that the EanI/R up regulates a conjugal transfer gene traF , a gene important for plasmid transfer in P. ananatis LMG 2665 T ( Table 3 ).…”
Section: Discussionmentioning
confidence: 99%